Bit-Sliced Implementation of SM4 and New Performance Records - Xin Miao; Lu Li; Chun Guo; Meiqin Wang; Weijia Wang (IET Information Security)
SM4 is a popular block cipher issued by the Office of State Commercial Cryptography Administration (OSCCA) of China. In this paper, we use the bit-slicing technique that has been shown as a powerful strategy to achieve very fast software implementations of SM4. We investigate optimizations on two frontiers. First, we present a more efficient bit-sliced representation for SM4, which enables running 64 blocks in parallel with 256-bit registers. Second, we describe an optimized algorithm for data form transformations, also allowing efficient implementations of SM4 under Counter (CTR) mode and Galois/Counter mode. The above optimizations contribute to a significant performance gain on one core compared with the state-of-the-art results. This work is an extension of the conference paper at Inscrypt 2022, awarded the best paper award.